Investigating the link between HPV genotypes and cervical abnormality incidence in women with HPV infections: insights from a leading referral centre - Zahra Sadeghi; Amir Aboofazeli; Sheida Sarrafzadeh; Naeimeh Tayebi; Roxana Tajdini; Fariba Yarandi; Seyed Mohammad Jazayeri (Virology Journal)
Abstract Background Cervical cancer (CC) is a serious health issue, especially in low- and middle-income countries, primarily caused by human papillomavirus (HPV) infection, particularly genotypes 16 and 18. Other risk factors include smoking, early sexual activity, and long-term oral contraceptive use. Early detection through cervical cytology and HPV testing is vital for effective prevention. Objective This study aimed to analyze the clinical and epidemiological characteristics of cervical intraepithelial neoplasia (CIN) in HPV-positive women at a Tehran teaching hospital, focusing on HPV genotypes and their association with CIN. Methods We conducted a cross-sectional study of HPV-positive women who underwent Pap smear testing, HPV genotyping via real-time PCR, and colposcopy with biopsies of suspected lesions. Risk factors like smoking and alcohol consumption were evaluated, and statistical analyses were performed, including ordinal logistic regression. Results Among participants, 52.4% had abnormal CIN: CIN I (31.1%), CIN II (11.4%), and CIN III (10.0%). HPV-16 was the most prevalent genotype (43.7%), significantly associated with severe CIN outcomes (odds ratio [OR] = 2.88, 95% CI), followed by HPV-18 (OR = 1.87, 95% CI). Smoking increased the risk of severe CIN (OR = 1.53, 95% CI), while older age and later age at sexual debut correlated with better CIN outcomes. Conclusions HPV-16 and smoking are major predictors of severe CIN, highlighting the need for targeted interventions such as HPV vaccination and smoking cessation, along with regular screenings to lower cervical cancer risks. Additional research is required to evaluate the persistence of different HPV genotypes and their progression to CIN and cervical cancer.”